Counseling on Scabies Skin Disease at Al-Ikhwan Islamic Boarding School, Mekar Jaya Village, Muaro Jambi Regency - Annisa Rezi Ritami; Rahadina Rizkika; Nurul Atika; Sela Tresia; Galih Dimas Saputra; Jelly Permatasari (Rifa'Institute, 2022)
The prevalence of scabies in Indonesia is 4.6% - 12.95% and is the third of the 12 most common skin diseases that occur in the community, especially in densely populated residential areas such as TPA (Children's Education Park), prisons, barracks, flats and Islamic boarding school. The number of people with scabies skin disease in Islamic boarding schools needs good treatment and prevention in order to reduce sufferers of this skin disease in Islamic boarding schools. Based on a survey at the Al-Ikhwan Islamic boarding school located in Mekar Jaya Village, Muaro Jambi, it is known that scabies is one of the most common diseases suffered by the students at this Islamic boarding school.